The Influence of Leadership on Job Satisfaction of Members of The Indonesian Democratic Party of Struggle in Riau Province: The Role of Interpersonal Communication Mediation - Jeki; Rahmat, Adi; Fatkhurahman (Yayasan Education Al Aqsho Modern, 2023)
This study aims to investigate the effect of leadership on job satisfaction of members of the Indonesian Democratic Party of Struggle (PDIP) in Riau Province and examine the mediating role of interpersonal communication in the relationship. This research was conducted by collecting data from active PDIP members in Riau Province through the use of questionnaires. The research sample consisted of 100 randomly selected respondents. The results of data analysis using Structural Equation Modeling (SEM) processed using SmartPLS 3.2.9 for data processing show that leadership has an insignificant influence on job satisfaction of PDIP members in Riau Province. In addition, interpersonal communication was also found to have a significant mediating role between leadership and job satisfaction of PDIP members. This suggests that interpersonal communication is an important factor in linking effective leadership with higher levels of job satisfaction. The findings of this study have important implications for political party management and party leaders in developing effective leadership strategies and increasing the job satisfaction of party members. Improved interpersonal communication is also key in facilitating good relationships between leaders and party members, which in turn can contribute to higher job satisfaction. However, this study has several limitations, including geographical restrictions and a research population limited to PDIP members in Riau Province. In addition, the use of questionnaires as a data collection method may also affect the results of the study. Therefore, future research can involve a more representative sample and use different data collection methods to expand the generalizability of the research results